Sexuality: Myths, Fears, Perceptions and Challenges towards Sex Education - Ngunya , Cecilia Seba; Kariuki , Jane (African Journal of Education,Science and Technology (AJEST), 2025)
Sexuality is an important subject as it forms an integral part of each person’s identity. The goals of comprehensive sexuality education are to help young people gain a positive view of sexuality and to provide them with developmentally appropriate knowledge and skills so that they can make healthy decisions about their sex lives now and in the future. It encompasses sexual development, reproductive health, interpersonal relationships, affection, intimacy, body image, and gender roles. Knowledge on sexuality also addresses the biological, socio-cultural, psychological and spiritual dimensions of sexuality. However, due to mixed perceptions, sexuality education has received resistance in its introduction to Kenyan Education system. Furthermore, existing studies on this subject reports fragmented information about the factors contributing to this resistance. In this review paper, the challenges facing the promotion of sexuality education are systematically investigated and brought into perspective. The paper focuses on the myths, fears, perceptions and challenges towards sex education. By addressing these blocks to full introduction of sexuality education in Kenyan Education system, the paper will help Kenyans to gain knowledge that Sexuality education is the lifelong process of acquiring information and forming attitudes, beliefs, and values about identity, relationships, and intimacy. The paper is intended for curriculum developers in identifying avenues of reintroducing sexuality education which will further contribute to knowledge management. Parents and guardians are also targeted in gaining knowledge as they are the primary sexuality educators of their children. The findings conclude that if children are provided with accurate information in school and home, they will be equipped with the tools to make wise and healthy decisions about their sexuality.